Structural transformations in graphene studied with high spatial and temporal resolution - Warner, J; Rümmeli, M; Ge, L; Gemming, T; Montanari, B; Harrison, N; Büchner, B; Briggs, G (2009)
Graphene has remarkable electronic properties, such as ballistic transport and quantum Hall effects, and has also been used as a support for samples in high-resolution transmission electron microscopy and as a transparent electrode in photovoltaic devices. There is now a demand for techniques that can manipulate the structural and physical properties of graphene, in conjunction with the facility to monitor the changes in situ with atomic precision. Here, we show that irradiation with an 80kV electron beam can selectively remove monolayers in few-layer graphene sheets by means of electron-beam-induced sputtering. Aberration-corrected, low-voltage, high-resolution transmission electron microscopy with sub-ngström resolution is used to examine the structural reconstruction occurring at the single atomic level. We find preferential termination for graphene layers along the zigzag orientation for large hole sizes. The temporal resolution can also be reduced to 80ms, enabling real-time observation of the reconstruction of carbon atoms during the sputtering process. We also report electron-beam-induced rapid displacement of monolayers, fast elastic distortions and flexible bending at the edges of graphene sheets. These results reveal how energy transfer from the electron beam to few-layer graphene sheets leads to unique structural transformations. © 2009 Macmillan Publishers Limited.